2012
DOI: 10.1590/s0103-21002012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de aleitamento materno e fatores associados no município de Londrina-PR

Abstract: Objective: To describe breastfeeding prevalence and associated factors, in the municipality of Londrina, PR, Brazil. Methods: This quantitative, descriptive study included interviews of 770 companions of children younger than 12 months of age during an anti-polio vaccination campaign in August 2008. Results: A total of 72.5% of the children were breastfed in the first hour after birth; 33.8% were exclusively breastfed from zero to six months of age, 53.7% until the fourth month and 7.8% until the sixth month; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1
36

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 22 publications
2
6
1
36
Order By: Relevance
“…Com relação ao AME os estudos analisados indicam redução gradativa ao longo dos meses de vida da criança, com uma prevalência de até 60% no primeiro mês (KAUF-MANN et al, 2012), com percentuais menores do segundo ao quinto mês (KAUFMANN et al, 2012;QUELUZ et al, 2012;SANCHES et al, 2011;VIEIRA et al, 2010) e que não chegam aos 40% no sexto mês (BERNARDI; GAMA; VITOLO, 2011;LEONE;SADECK, 2012;SALUSTIANO et al, 2012;SOUZA et al, 2012).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Com relação ao AME os estudos analisados indicam redução gradativa ao longo dos meses de vida da criança, com uma prevalência de até 60% no primeiro mês (KAUF-MANN et al, 2012), com percentuais menores do segundo ao quinto mês (KAUFMANN et al, 2012;QUELUZ et al, 2012;SANCHES et al, 2011;VIEIRA et al, 2010) e que não chegam aos 40% no sexto mês (BERNARDI; GAMA; VITOLO, 2011;LEONE;SADECK, 2012;SALUSTIANO et al, 2012;SOUZA et al, 2012).…”
Section: Discussionunclassified
“…O trabalho materno fora de casa, o retorno ao trabalho após o parto e o trabalho sem licença-maternidade foram relacionados a uma maior chance de interrupção do aleitamento materno nos estudos (CARRASCOZA et al, 2011;DEMÉTRIO;PINTO;ASSIS, 2012;LEONE;SADECK, 2012;QUELUZ et al, 2012;SALUSTIANO et al, 2012). Do mesmo modo, o uso de chupetas antes dos seis meses de vida foi descrito como fator potencial relacionado ao desmame, sendo observada a manutenção do AM 2,4 vezes mais frequente em crianças sem hábito de usar chupeta (CARRASCOZA et al, 2011;LEONE;SADECK, 2012;KAUFMANN et al, 2012;MARTINS;GIUGLIANI, 2012;SALUSTIANO et al, 2012;SANCHES et al, 2011;SOUZA et al, 2012;VIEIRA et al, 2010).…”
Section: Fatores Que Se Relacionam Ao Desmame Precoce: Implicações Maunclassified
See 2 more Smart Citations
“…Another study, however, identified different risk factors for not maintaining EBF up to the sixth month of life: the use of pacifiers and artificial nipples, maternal age, low maternal educational level, primiparity, and low birth weight; the prevalence of BF was most significant between the first and fourth months of life, undergoing a sharp fall in the fourth (53.7%) to the fifth month (7.8%) (18) .…”
Section: Discussionmentioning
confidence: 99%